Mercury interaction with S-containing molecules: implications for methylation and demethylation processes in a sulfate reducing bacteria - Bakour, Ikram; Isaure, Marie-Pierre; Barrouilhet, Sophie; Goñi-Urriza, Marisol; Monperrus, Mathilde (Frontiers in Environmental Chemistry, 2025)
Mercury methylation by anaerobic microorganisms, including sulfate-reducing bacteria (SRB), is a key process in the production of neurotoxic methylmercury (MeHg). The chemical speciation of mercury (Hg) strongly influences its bioavailability as well as its potential for methylation and demethylation, with sulfur-containing ligands playing a critical role in these processes. In this study, we used isotopically enriched mercury species (199Hg(II), Me202Hg) to investigate how molecular speciation of mercury affects both methylation and demethylation processes by the sulfate-reducer Pseudodesulfovibrio hydrargyri BerOc1. Experimental assays were carried out: (i) without external addition of S-ligands, (ii) with the addition of increasing concentrations of exogenous cysteine (Cys) (0.01, 0.1, and 0.5 mM), or (iii) with the addition of exogenous sulfide (0.1 mM). We showed that the highest methylation rate (Kmeth) was obtained without the external addition of S-ligands, whereas the addition of Cys or sulfide decreased Hg methylation regardless of Cys concentration. By quantitatively determining Hg(II) speciation in extracellular fractions, we demonstrated that Hg(II) was mostly present in the form of Hg(Cys)2, when Cys was added. However, metabolically sulfide production from Cys degradation shifted the chemical speciation of Hg(II) from Hg(Cys)2 to a more insoluble fraction (HgS(S)). In the assay without externally added ligands (Cys or sulfide), speciation models were generated by taking in account the metabolically produced thiols. These models established the predominance of Hg(II) complexes with a mixed ligation involving biosynthesized thiols, OH−, and Cl− ions. Our results suggest that these complexes with lower thermodynamic stabilities enhance the MeHg formation rate compared to the more stable Hg(Cys)2 or HgS(s) species. Unlike Hg(II) methylation, the addition of S-ligands did not affect the rates of demethylation (Kdemeth) of MeHg, even though it caused a shift in the chemical speciation of MeHg (from MeHgCl to MeHgCys and MeHgSH). These findings contribute to our understanding of the potential role of specific S-ligands and chemical speciation in governing the environmental fate and toxicity of mercury.